Exploring the scientific literature on controversial and timely ecological questions - Buonocore, Elvira; Aricò , Salvatore; Napolitano, Gaetana; Rendina, Francesco; Grande, Umberto; Franzese, Pier Paolo (Ecological Questions, 2024)
The structure and functioning of the world’s ecosystems have changed more rapidly during the last fifty years than at any time in the human history due to direct and indirect anthropogenic drivers. Global indicators of ecosystem extent and condition have shown a decrease by an average of 47% of their estimated natural baselines, with many ecosystems continuing to decline by at least 4% per decade (IPBES, 2019). These changes occurring in marine and terrestrial ecosystems are mostly driven by socio-economic systems run on unsustainable natural resources extraction and consumption . The unsustainable exploitation of natural capital stocks poses serious questions about long-term human and ecosystems health. Indeed, the loss of biological diversity can alter the functioning of ecosystems and their ability to provide society with flows of goods and services vital for human well-being. Over the past decades, there have been increasing research efforts to explore the interplay between humans and nature, focusing on the development of an ecosystem approach for studying human-environment interactions by means of a system-based and interdisciplinary approach to science. Human and systems ecology play a key role in this regard, but also other biological disciplines can support the development of a full awareness about the interdependence of healthy ecosystems and human well-being. This transdisciplinary knowledge is important from a scientific viewpoint and it can also better support environmental policies and decision making